ANALISIS PRODUKTIVITAS DAN RENTABILITAS EKONOMI USAHA MIKRO, KECIL DAN KOPERASI DI KECAMATAN PIYUNGAN BANTUL - Mujino Mujino (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2015)
This research purpose to analize productivity and economic rate of return on small, midle and Cooperative enterprise in Piyung rigion. Productivity and  economic rate of return index are very importance to measure output and input on production process, and asset effectivness. In generally productivity and economic rate of return are low, althought we  are sustainable in business. I want to known, what factors are influence in business and motivation their  have. Indonesia have a great micro, small, midle and cooperatve enterprise. Base on statistics 99.8% consist of its enterprise and 0,2 % is big enterprise. They are contribution on lobour obsorb and  social safety net.  Sample size are sixty   got from three subrigions in Piyungan as : Sitimulyo, Srimartani and Srimulyo, with stratified random sampling. Research data are from small, midle and cooperative enterprise, who have business in various item. Discriptive statistic model we use on research problem, ratios as index productivety and  economic rate of return  to mesure businessment performent. The following are statistic index : productivety 16,56%,, economic rate of return 8.02%, businessmen 7.300 or 14,68%., jobless 8.105 or 16,30% and population amoun 49.711.